Ruptured Splenic Artery Aneurysm: Rare Cause of Shock Diagnosed with Bedside Ultrasound - Davis, Terri (West J Emerg Med, 2015)
Splenic artery aneurysm rupture is rare and potentially fatal. It has largely been reported in pregnant patients and typically not diagnosed until laparotomy. This case reports a constellation of clinical and sonographic findings that may lead clinicians to rapidly diagnose ruptured splenic artery aneurysm at the bedside. We also propose a rapid, but systematic sonographic approach to patients with atraumatic hemoperitoneum causing shock. It is yet another demonstration of the utility of bedside ultrasound in critically ill patients, specifically with undifferentiated shock.